Interaction of Fertilization and Weed Control Influences on Growth, Biomass, and Carbon in Eucalyptus Hybrid (E. pellita × E. brassiana) - Pandu Yudha Adi Putra Wirabuana; Ronggo Sadono; Sergian Juniarso; Fahmi Idris (Institut Pertanian Bogor (IPB University), 2020)
Fertilization and weed control are regularly conducted as the main silvicultural prescriptions in the eucalyptus plantation forest. However, the interaction effects of both treatments on eucalyptus performance are still not deeply understood, even though these treatments require high investment. This circumstance may potentially inhibit the managers to formulate more efficient maintenance strategy for increasing stand productivity. This study examined the interaction effects of fertilization and weed control on growth, biomass, and carbon storage in eucalyptus hybrid (E. pellita x E. brassiana). Results demonstrated that without both treatments, the average stand volume only reached 37.9 m3 ha -1 with the mean biomass and carbon storage approached 25.4 and 12.7 Mg ha -1, respectively. In contrast, the use of both treatments simultaneously improved the mean volume around 60.4 m3 ha -1 with the average biomass and carbon storage closed to 37.6 and 18.8 Mg ha -1. Furthermore, the development of eucalyptus hybrid using fertilization without weed control only gained the mean wood production approximately 58.7 m3 ha -1 while the practice of weed control without fertilization only resulted the average volume nearly 43.7 m3 ha -1. These facts indicated fertilization exhibited higher influence than weed control on the performance of eucalyptus hybrid.